2017
DOI: 10.1051/epjconf/201714401010
|View full text |Cite
|
Sign up to set email alerts
|

Site Characterization of the Northern Site of the Cherenkov Telescope Array

Abstract: Abstract. We present the current knowledge and activities to assess the climatology of the "Observatorio del Roque de los Muchachos" (ORM), selected to host the Northern observatory of the CTA, with particular emphasis on molecular density profiles and aerosol extinction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…1958). The GDAS data are provided for a grid of integer latitude and longitude (in degrees), hence the closest grid point for the MAGIC telescope corresponds to 29 • N and 18 • W. The GDAS predictions have been ground-validated with the MAGIC weather station resulting in excellent agreement of the predicted pressure values and a small positive bias of two degrees for the temperatures (Gaug et al 2017), attributed to local ground cooling effects at night, which is not reproduced at the GDAS grid point, located over the Sea. A more accurate local modelling of the molecular profile involving the Weather Research and Forecasting (WRF) 2 is currently investigated, but out of the scope of this article.…”
Section: Subtraction Of the Molecular Profilementioning
confidence: 99%
“…1958). The GDAS data are provided for a grid of integer latitude and longitude (in degrees), hence the closest grid point for the MAGIC telescope corresponds to 29 • N and 18 • W. The GDAS predictions have been ground-validated with the MAGIC weather station resulting in excellent agreement of the predicted pressure values and a small positive bias of two degrees for the temperatures (Gaug et al 2017), attributed to local ground cooling effects at night, which is not reproduced at the GDAS grid point, located over the Sea. A more accurate local modelling of the molecular profile involving the Weather Research and Forecasting (WRF) 2 is currently investigated, but out of the scope of this article.…”
Section: Subtraction Of the Molecular Profilementioning
confidence: 99%
“…to assess the range of variation of t µ,mol due to changes in the atmospheric profile for the LST, we used the data of one full year from the "Global Data Assimilation System" (GDAS) "Final Analysis" database 16 for the closest grid point to La Palma, whose temperature and pressure predictions show excellent correlation with the measurements of the MAGIC weather station (Gaug et al 2017), apart from a constant 2 • C bias, which can be corrected. The full height-resolved temperature and pressure profiles were used to derive B µ for fixed telescope efficiencies ξ det ( ) for the LST.…”
Section: Atmospheric Transmissionmentioning
confidence: 99%
“…The MAGIC Collaboration has found that the altitude profile of the aerosol extinction coefficient for clear nights is exponential with a scale height of H aer ≈(500-700) m (Gaug et al 2017), with an aerosol optical depth (AOD) on the ground of about (AOD≈ 0.02) on average, however ranging from practically zero to almost 0.1 for normal clear nights.…”
Section: Aerosol Transmission -mentioning
confidence: 99%
“…The scattering probability becomes radially symmetric in such a case. To estimate the dependency of N (h)/Ns on altitude, we use a typical atmospheric winter condition at the ORM 8 (Gaug et al 2017) with: Aerosols scatter light more efficiently than molecules and usually less isotropically, due to their larger sizes, although they are much less in number density. World-class astronomical observatories are however characterized by extremely low aerosol contamination on average.…”
Section: Scattering Of the Laser Light In The Lower Atmospherementioning
confidence: 99%
“…World-class astronomical observatories are however characterized by extremely low aerosol contamination on average. For instance, typical winter nights on La Palma show aerosol optical thicknesses (AOTs) of the ground layer of the order of only 0.02 at λ = 532 nm, with extinction coefficients distributed exponentially with a scale height of around Haer ≈ 500 m (Gaug et al 2017), hence:…”
Section: Scattering Of the Laser Light In The Lower Atmospherementioning
confidence: 99%